ARL3, a small GTPase with a functionally conserved role in primary cilia and immune synapses. (4th May 2021) - Powell, Laura; Samarakoon, Youhani H.; Ismail, Shehab; Sayer, John A.
ABSTRACT: The primary cilium and the immunological synapse are both specialized functional plasma membrane domains that share several similarities. Signalling output of membrane domains is regulated, spatially and temporally, by segregating and focusing lipids and proteins. ARL3, a small GTPase, plays a major role in concentrating lipid-modified proteins in both the immunological synapse and the primary cilia. Here in this review we will introduce the role of ARL3 in health and disease and its role in polarizing signalling at the primary cilia and immunological synapses.